Standardization of rapid multiplication protocol in petaloid male sterile lines of African marigold (Tagetes erecta) through in vitro culture - KUMAR, K RAVINDRA; SINGH, KANWAR PAL; RAJU, D V S; PANWAR, SAPNA; BHATIA, REETA; JAIN, P K; VINOD, VINOD (The Indian Journal of Agricultural Sciences, 2017)
Marigold (Tagetes erecta L.) is one of the farmerâ€™s first choice for commercial cultivation. It is commonly propagated through seeds, but some ornamentally high valued petaloid and gynomonoecious lines can only be maintained through vegetative propagation. Therefore, the objective of the present investigation was to develop efficient in vitro protocol for mass multiplication of commercially high valued petaloid male sterile cultivars. Nodal segments were chosen as explant from two thermotolerant marigold cultivars, viz. Siracole Orange and Siracole Yellow. Explants were pre-treated with carbendazim (0.2%) + metalaxyl (0.2%) + 8-hydroxy quinoline citrate (200 mg/l) for 60 min followed by surface sterilization with 0.1% HgCl2 for 4 min to eliminate the microbial contamination. Highest culture establishment (82.2%) and earliest bud emergence (3.88 days) was recorded in Murashige and Skoog (MS) medium supplemented with BAP (0.5 mg/l) and NAA (0.05 mg/l). Maximum (6, 28, 122 and 404 shoots/explant) proliferation with healthy shoots and free from callus was obtained on MS medium supplemented with 0.5 mg/l BAP + 0.1 mg/l NAA + 2.5 mg/l AgNO3 in 30, 60, 90 and 120 days after culture respectively. Maximum elongation (2.10 cm) was observed on MS media devoid of growth regulators (control). Highest rooting percentage (96.50%), maximum number of roots (23.37), rapid root induction (5.25 days) and high ex vitro survival (91.25%) was noted in Â½ MS medium supplemented with 0.5 mg/l IBA. Highest plant survival (98.10%) and superior plant growth was observed when rooted plants were shifted to low-cost polypropylene glasses instead of traditional glass bottle system. This protocol is highly useful for mass multiplication of true-to-type, disease free planting material as well as helpful in long term maintenance of germplasm lines.